Applications of Lac Dye Using Different Mordants on Leather - Inayat, Asma; Khalid, Bushra; Liaquat, Lubna; Yaqub, Azra (Biological Sciences - PJSIR, 2008)
. Lac dye aleuritic acid extracted from seed lac, when applied onto leather, using post-mordanting process showed good results. Among acetic acid, formic acid and alum, acetic acid at 0.1 M concentration proved to be the best mordant and gave excellent colour fastness to washing, light and rubbing and good tensile strength.